Level of Compassion Satisfaction and Compassion Fatigue Among Selected Teachers in the Philippines and the United States of America - Amoma, Mitzi E.; Asunto, Ivory V.; Carba, Michelle C.; Hernandez, Jayson H.; Macias Jr, L Arturo O.; Culi-Macias , Fritzie; Menguito, Bennet James; Pabustan, Noemi B.; Tadlip, Ricky S.; Tumaliuan, Rhodora R. (Randwick International of Education and Linguistics Science Journal, 2025)
Teachers’ compassion often motivates them to go the extra mile in supporting their students, which provides personal and professional satisfaction. However, this dedication can also lead to compassion fatigue, manifested as burnout and secondary traumatic stress. This study aimed to identify the levels of compassion satisfaction and compassion fatigue among teachers and examine their relationship with demographic profiles, including age, sex, years of teaching experience, and the country of current employment. A standardized questionnaire was administered via Google Forms to 50 teachers from the United States and the Philippines using purposive sampling. The study employed a descriptive-comparative research design. Descriptive statistics, including percentages and mean scores, were used to summarize the data, while the Mann-Whitney U Test and Kruskal-Wallis Test were applied to determine significant differences between groups. Results indicate that the majority of respondents are female, aged between late 30s to 40s, and have more than five years of teaching experience. Overall, teachers reported experiencing compassion satisfaction “very often,” suggesting a high sense of fulfillment in their roles as compassionate educators. In contrast, burnout and secondary traumatic stress were rated as “sometimes,” indicating variability in the experience of compassion fatigue. Significant differences were observed in compassion satisfaction across age groups and years of teaching experience, with older and more experienced teachers reporting higher satisfaction. Burnout was more prevalent among teachers in the United States, whereas secondary traumatic stress was more pronounced among teachers in the Philippines. Based on these findings, the study recommends strategies to minimize and manage compassion fatigue among teachers, thereby enhancing their well-being and sustaining their professional effectiveness.